Program Saibatin Solusi Peningkatan Level Keberdayaan Kader Posyandu dan Ibu Hamil tentang Pemberian ASI Eksklusif - Ningsih, Dewi Ayu; Sari, Nirma Lidia; Puteri, Hidayatusy Syukrina (Universitas Baiturrahim, 2025)
The SAIBATIN Program is a community empowerment model designed to enhance the success of exclusive breastfeeding through 42-day postpartum assistance provided by trained posyandu (community health post) cadres. This activity was implemented as part of the Community Partnership Empowerment Program (PKM) funded by the Directorate of Research and Community Service (DPPM), Directorate General of Research and Development, Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, in 2025. The program activities included stakeholder engagement, breastfeeding preparedness education for pregnant women, training for posyandu cadres on best practices in exclusive breastfeeding, and postpartum breastfeeding assistance conducted by the cadres. Evaluation using pre- and post-test methods showed a significant increase in knowledge scores among both cadres and pregnant women, with an average improvement of 24–25%. Cadres also demonstrated enhanced practical skills in breastfeeding counseling and maternal assistance. The SAIBATIN Program proved effective in strengthening the capacity of cadres and mothers to support exclusive breastfeeding success. This model has strong potential to be replicated as a posyandu-based community empowerment strategy to help achieve national maternal and child health targets